The Algorithmic Heart: What is the Future of AI in Cardiology? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The Algorithmic Heart: What is the Future of AI in Cardiology? Introduction The convergence of Artificial Intelligence (AI) and cardiovascular medicine ...
Keywords: Drug Discovery; Diagnostics; Artificial Intelligence; Healthcare Innovation; Precision Medicine